2020
DOI: 10.1108/jsocm-09-2019-0142
|View full text |Cite
|
Sign up to set email alerts
|

Building positive resilience through vulnerability analysis

Abstract: Purpose The purpose of this paper is to propose an integrative framework for vulnerability analysis in social marketing systems by identifying, investigating and problematising the relationships among several interrelated concepts, including power, power asymmetry, vulnerability and resilience, in the context of social marketing systems. Design/methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 62 publications
0
20
0
1
Order By: Relevance
“…Vulnerability is, thus, not a secluded entity and in opposition to resilience, which marks the desirable state. Whereas resilience is, per definition, embedded in the context of adversity and, thus, potential vulnerability ( Werner, 2005 ; Rutter, 2012 ; Juen and Siller, 2013 ; Luthar et al, 2015 ; Baiasu, 2020 ; Kubacki et al, 2020 ), vulnerability is hardly understood as an integral part of resilience ( Baiasu, 2020 ). Thus, future endeavors should focus on the meaning of vulnerability at the individual, systemic, and structural levels, and its implications for resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Vulnerability is, thus, not a secluded entity and in opposition to resilience, which marks the desirable state. Whereas resilience is, per definition, embedded in the context of adversity and, thus, potential vulnerability ( Werner, 2005 ; Rutter, 2012 ; Juen and Siller, 2013 ; Luthar et al, 2015 ; Baiasu, 2020 ; Kubacki et al, 2020 ), vulnerability is hardly understood as an integral part of resilience ( Baiasu, 2020 ). Thus, future endeavors should focus on the meaning of vulnerability at the individual, systemic, and structural levels, and its implications for resilience.…”
Section: Discussionmentioning
confidence: 99%
“…Investment into knowledge development, through dedication of the employees of both companies, influenced also on increase of trust and commitment, which were important factors of analysed project development. It refers to evolutionary development of business relationship, in which trust is developing in time (Lacoste & Johnsen, 2015;Siemieniako & Mitręga, 2018;Kubacki et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…As an example, Shi et al (2017) reported that highly vulnerable consumers may act more impulsively in the face of temptation which can lead to excess products being bought, and use gambling addictions and susceptibility to fraud as illustrations. In this way, vulnerable consumers' own behaviour in certain situations can increase disadvantage 13 (Kubacki et al, 2020). Therefore, vulnerability may not be a passive process, thus requiring detailed examination of consumer characteristics and context to determine representation.…”
Section: Principle 2: Representation and Outreachmentioning
confidence: 99%